2003
DOI: 10.1152/ajpendo.00210.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine-phosphatase 1B activation is regulated developmentally in muscle of neonatal pigs

Abstract: Suryawan, Agus, and Teresa A. Davis. Protein-tyrosine-phosphatase 1B activation is regulated developmentally in muscle of neonatal pigs. Am J Physiol Endocrinol Metab 284: E47-E54, 2003. First published September 11, 2002 10.1152/ajpendo.00210.2002The high activity of the insulin-signaling pathway contributes to the enhanced feeding-induced stimulation of translation initiation in skeletal muscle of neonatal pigs. Protein-tyrosine-phosphatase 1B (PTP1B) is a negative regulator of the tyrosine phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Therefore, we conducted a detailed study of the role of development in the activation and protein abundance of these signaling components. We determined that the activation of PTP1B, PTEN, PP2A, and TSC2, all negative regulators of insulin signaling, are low in muscle of neonatal pigs and increase with age, consistent with a developmental decrease in the activation of the pathways that promote translation initiation (Suryawan and Davis, 2003;Suryawan et al, 2006). However, we were able to detect an effect of feeding only on TSC2 in which feeding decreased the activation of TSC2 and this effect of feeding was attenuated with age.…”
Section: Postnatal Ontogeny Of the Insulin And Amino Acid Signaling Pmentioning
confidence: 68%
“…Therefore, we conducted a detailed study of the role of development in the activation and protein abundance of these signaling components. We determined that the activation of PTP1B, PTEN, PP2A, and TSC2, all negative regulators of insulin signaling, are low in muscle of neonatal pigs and increase with age, consistent with a developmental decrease in the activation of the pathways that promote translation initiation (Suryawan and Davis, 2003;Suryawan et al, 2006). However, we were able to detect an effect of feeding only on TSC2 in which feeding decreased the activation of TSC2 and this effect of feeding was attenuated with age.…”
Section: Postnatal Ontogeny Of the Insulin And Amino Acid Signaling Pmentioning
confidence: 68%
“…These responses decrease with development in parallel with the decline in muscle protein synthesis (48,50,58). Furthermore, the activity of PTP1B, an inhibitor of the insulin-signaling pathway, increases with development, consistent with the developmental decline in insulin sensitivity during the early postnatal period (49). Here, we report a more detailed study of the role of development in the feeding-induced activation and protein abundance of signaling components that are upstream of mTOR, as well as downstream targets of mTOR, in skeletal muscle and liver of neonatal pigs.…”
mentioning
confidence: 60%
“…We (37)(38)(39) have previously found that the activation of early steps in the insulin-signaling pathway upstream of PKB is induced by feeding. In this study, we investigated the separate effects of amino acids and insulin on the phosphorylation of PKB at Ser 473 , an important component of the insulin-signaling pathway (Fig.…”
Section: Resultsmentioning
confidence: 99%